Analysis of Differences in Long-Term Financial Performance Before and After Stock Split in Companies Listed on the Indonesia Stock Exchange in 2015-2020 - Hadid Hidayat; Selamet Riyadi (Ridwan Institute, 2022)
This study aims to examine differences of the company's financial performance as indicated by the Current Ratio (CR), Debt to Total Assets (DAR), Total Asset Turnover (TATO), Return on Assets (ROA), Return on Equity (ROE) and Price Earnings Ratio. Data were obtained from 20 companies that conducted stock splits in 2017 and 2018. The difference test was carried out using Man Whitney using SPSS 25 software. The results showed that the current ratio (CR) did not show a significant difference between 3 years before and 3 years after the stock splits. Debt to total assets (DAR) did not show a significant difference between 3 years before and 3 years after the stock split. Total asset turnover (TATO) did not show a significant difference between 3 years before and 3 years after the stock split. This result is significant at the 10% alpha or 90% confidence interval. Return on assets (ROA) shows a significant difference between 3 years before and 3 years after the stock split. Return on equity (ROE) shows a significant difference between 3 years before and 3 years after the stock split. Price earnings ratio (PER) does not show a significant difference between 3 years before and 3 years after the stock split.